A few-shot U-Net deep learning model for lung cancer lesion segmentation via PET/CT imaging. (1st March 2022) - Protonotarios, Nicholas E; Katsamenis, Iason; Sykiotis, Stavros; Dikaios, Nikolaos; Kastis, George A; Chatziioannou, Sofia N; Metaxas, Marinos; Doulamis, Nikolaos; Doulamis, Anastasios
Abstract: Over the past few years, positron emission tomography/computed tomography (PET/CT) imaging for computer-aided diagnosis has received increasing attention. Supervised deep learning architectures are usually employed for the detection of abnormalities, with anatomical localization, especially in the case of CT scans. However, the main limitations of the supervised learning paradigm include (i) large amounts of data required for model training, and (ii) the assumption of fixed network weights upon training completion, implying that the performance of the model cannot be further improved after training. In order to overcome these limitations, we apply a few-shot learning (FSL) scheme. Contrary to traditional deep learning practices, in FSL the model is provided with less data during training. The model then utilizes end-user feedback after training to constantly improve its performance. We integrate FSL in a U-Net architecture for lung cancer lesion segmentation on PET/CT scans, allowing for dynamic model weight fine-tuning and resulting in an online supervised learning scheme. Constant online readjustments of the model weights according to the users' feedback, increase the detection and classification accuracy, especially in cases where low detection performance is encountered. Our proposed method is validated on the Lung-PET-CT-DX TCIA database. PET/CT scans from 87 patients were included in the dataset and were acquired 60 minutes after intravenous 18 F-FDG injection. Experimental results indicate the superiority of our approach compared to other state-of-the-art methods.